Gender Empowerment Analysis in Coastal Community Households Around Mangrove Ecosystem in Western Papua - Handayani, Handayani; Poltak, Hendra; Ismail, Ismail; Muhfizar, Muhfizar (Jurnal Sosial Ekonomi Kelautan dan Perikanan, 2023)
Gender empowerment is a key aspect of Indonesia’s national development, highlighted by Presidential Instruction No. 9 of 2000 which advocates gender mainstreaming in all life sectors. The instruction’s goal is to ensure equal participation and benefit-sharing between women and men in various fields including politics, economy, culture, and security. This study evaluates gender empowerment in West Papua’s mangrove ecosystem communities, focusing on productive and reproductive roles, as well as resource access and control. Conducted in Sorong City, Sorong Regency and South Sorong Regency, this research involved 140 respondents who were active in production and household activities related to the mangrove ecosystem. The Harvard model was used for analyzing gender roles in production and reproduction, identifying activity profiles, and access and control factors. Findings reveal a gender division in activities: reproductive tasks are mainly performed by women (50.31%), while productive tasks are predominantly men’s domain (62.94%). Men also largely control resources, with 70.54% access and 64.74% control. The study also correlates household characteristics with gender empowerment, noting reproductive activities’ impact (36.32%) and productive activities’ influence (22.54%). Focus group discussions corroborated questionnaire results, underscoring the need for government intervention. This intervention should include fisheries extension services providing information access, empowering women through economic and social skill enhancement, and ensuring their equal role in decision-making. The study also highlights the importance of educational access, advocating for awareness of its benefits and the establishment of schools near coastal communities. This approach aims to balance gender roles and participation in both economic and social activities.